Misrepresentation and misrepresentation of the verses of Hadiqat al-Haqiqa in corrected texts (Based on ancient manuscripts) - seyed mehdi tabatabaei (تاریخ ادبیات)
Any misinterpretation of the word or combination by the scribe and "correction" can lead to semantic ambiguity of the text, and it makes it difficult for the audience to understand the meaning of the poem. In addition, writing descriptions and suspensions on these inaccurate recordings leads to a more sophisticated concept of verses. The effect of these issues on correcting a text is multiplied when the book is corrected from ancient Persian literature, and the use of inappropriate and sometimes derogatory words is used. This claim can be traced back to Sana'i's Hadiqat al-Haqiqa; text that is difficult in itself, and various books and corrections have added to its difficulty, as far as can be seen in the corrected texts, the recorded form of some verses does not provide a clear meaning. This study seeks to highlight the inaccurate recording of some of the verses of this poem by using ancient manuscripts in a descriptive-analytical manner. The most important achievement of the research is suggestions for correctly recording or correctly reading some of the words, combinations and verses in the Sana'i Hadiqat al-Haqiqa, whereby the conceptual node of the verses in question will be resolved.